Reducing poverty and sustaining the environment : the politics of local engagement - Bass, Stephen, 1958- (Earthscan, 2005)
'A valuable contribution to our collective knowledge about governance poverty and the environment' Frances Seymour World Resources Institute 'Detailed and realistic documentation of contemporary development and governance relationships and trends' Melissa Leach Institute of Development Studies There are growing signs that development work by governments aid agencies and non-government organisations ignores the fact that environmental quality matters to the poor. There are also indications that some environmental work is pushing 'people-out' protection methodologies. Yet recently an extensive r.